Kepemimpinan Pendidikan dan Kewenangan : Tinjauan Literatur Tentang Dinamika Kekuasaan dan Pengambilan Keputusan di Lingkungan Sekolah - M. Alfian Nur Afandi; M. Imammul Muttaqin (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Leadership in the context of education plays a crucial role in determining the direction and quality of decision-making in the school environment. This study aims to describe the concepts of educational leadership and authority, and analyse the dynamics of power in school decision-making. Using a literature review approach, this research identifies various factors that influence decision-making by school leaders, such as sources of authority and power dynamics. The results show that effective leadership in education depends not only on formal authority, but also on the ability to manage power wisely. The implications of this study provide recommendations for school leaders in improving the quality of leadership and decision-making and offer important insights for the development of better education policies in the future.